Incomplete Childhood Vaccination and Associated Factors Among Children Aged 12–23 Months; Assessment of Time-To-Corrected Missed Opportunity for Vaccination for Routine Immunization: Evidence from The Cameroon Demographic and Health Survey 2018 - Whegang, Y. S. (British Journal of Healthcare and Medical Research, 2023)
Background: Complete childhood vaccination remains poor in Sub-Saharan African countries. Although missed opportunity for vaccination (MOV) was found responsible for low coverage, median time-to-corrected is useful to assess delay in vaccination. We explored incomplete vaccination coverage, describe characteristics of children who experienced corrected MOV for all antigens, and estimate median survival time. Method: Secondary analyses of a sample of 1285 (total weights=1315.91) children aged 12 to 23 months with at least one vaccination date, was performed. A weighted survival Kaplan-meier curve was use to estimate median time-to-corrected MOV for for each vaccine. Multiple correspondance analysis (MCA) was called to describe characteristics of children with corrected MOV and incomplete vaccination. We used the YFV corrected MOV status in the MCA analysis as it had the highest probability of outcome. A binary logistic regression analysis was used to identify factors associated to both outcomes. Results: Median survival time ranged from 5 (OPV0) to 96 days (Penta3). For the YFV, it was 22 days, and 65 days for MCV1. MCA analysis revealed two main dimensions characterized mainly by: first, by children who experienced MOV for simultaneous vaccines, born to uneducated mothers with no occupation, who were in contact with health facility within 2 months after birth; second, by first of third bird order children, born to caregivers less than 24 years or more than 31 years, who either had an occupation skill, or were not working. Probability of corrected MOV decreases among caregivers less than 24 years, those who delivered at home and had no antenatal care. Factors associated to incomplete vaccination revealed a decrease in the odds: in children whose mothers attended health facility within 2 months after birth, mother’s age more than 31 years than less than 24 years and, an increase in the odds with children who had less than 5 contacts with the health facility. Conclusion: Enhance effort on strategies targetting mothers during their stay in the maternity, heads of households, and younger mothers, is needed to increase vaccination coverage among children. Caregivers should pay attention to child’s vaccination schedule, and complete each vaccine ontime.